x(x+2)+2(x-2)=1

Simple and best practice solution for x(x+2)+2(x-2)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x+2)+2(x-2)=1 equation:



x(x+2)+2(x-2)=1
We move all terms to the left:
x(x+2)+2(x-2)-(1)=0
We multiply parentheses
x^2+2x+2x-4-1=0
We add all the numbers together, and all the variables
x^2+4x-5=0
a = 1; b = 4; c = -5;
Δ = b2-4ac
Δ = 42-4·1·(-5)
Δ = 36
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{36}=6$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(4)-6}{2*1}=\frac{-10}{2} =-5 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(4)+6}{2*1}=\frac{2}{2} =1 $

See similar equations:

| 25q^2+15q+1=25q | | -9z+5=-5 | | 16x^2=2304 | | 12n+8=68 | | -7m=17+4 | | 4/9x+1/5x=87 | | 2.3+8(1.3x–4.75)=629.9. | | (7+i)-(6-4i)=0 | | 0=4x^2-5x-6-4x+3 | | 62/2x=10 | | X=4x^2-5x-6-4x+3 | | 2-5d=2 | | -22y=18 | | 3+1/5=x-12/25 | | v3− 17=–14 | | Y=5x2-20×-5 | | -5/g+3=-7 | | 2i+7=3i-4 | | y(2y+9)=-7 | | 28=8k+12-27k | | 160=1.8x-80 | | 0.2y-0.1y=7 | | 140+148+136+x+142+150+90=900 | | F=9/5x68+32 | | H(x+1)=7 | | 9=3y=34 | | n/56=16/32 | | 1/2*m-2=3 | | 5(6-u)= | | -7r=27+-55 | | 1/2*m-2=4 | | 1/2*m-2=6 |

Equations solver categories